BRCA2 Dysfunction Promotes Malignant Transformation of Pancreatic Intraepithelial Neoplasia - Wang, Qi; Liu, Hongrui; liu, Tingting; Shu, Shizhen; Jiang, He; Cheng, Shidan; Yuan, Yaozong; Yang, Weiguo; Wang, Lifu (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Pancreatic ductal adenocarcinoma (PDAC) is an almost lethal disease. Thus, it is important to better understand its genetic progression from normal cells through precancerous lesions pancreatic intraepithelial neoplasia (PanIN) to invasive pancreatic cancer. Carriers of a germline mutation in BRCA2 have an increased risk of developing PDAC when compared with the general population. The purpose of our study was to examine the role of BRCA2 dysfuction in the progression of PDAC. Here we generated a novel in vitro model of pancreatic carcinogenesis. Cancerous PanIN-BR1 cells were established by stable transduction with lentiviral-mediated BRCA2 RNA interference in PanIN cell isolated from mice with oncogenic KrasG12D. Our data showed that silencing of BRCA2 promoted cell proliferation, migration and invasion in vitro. The tumorigenic potential of PanIN-BR1 were assessed by xenograft tumor formation in BALB/c nude mice. The expression of PCNA , Snail and Slug in the tumor xenografts was detected by immunohistochemistry. The staining for PCNA, Snail and Slug in PanIN-BR1-formed xenograft tissue was significantly more intense than PanIN-formed xenograft tissue. Microarray assay was also performed. Based on gene expression profiling and further validation by real-time PCR and Western Blot, we found that the expression of Cyclinb2, Cyclina2, Twist1, Wisp1 and Cxcr4 revealed a significant increase in the PanIN-BR1 cells, however, the expression of p15, p16 and Wisp2 showed a significant decrease in the PanIN-BR1 cells, compared to the PanIN cells. Collectively, these data reported here demonstrate that BRCA2 may be a promising therapeutic targets for PDAC progression.
Keywords: Pancreatic carcinogenesis